2017
DOI: 10.5430/jbar.v6n2p15
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Research on the Impact of Online Shopping Return Policy on Consumer Behavior

Abstract: Based on the relevant literature, this paper study the impact of online shopping return policy on consumer purchase behavior from the dimension of return policy, consumer perception, consumer purchase behavior and so on. In the online shopping environment, the return problem between retailers and consumers is more obvious. Based on the researching achievements of predecessors, return policy can be divided into three dimensions: return cost, return time limit and efforts. Consumer psychological perception of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…У своїх працях дослідники [1] наголошують на значній ролі інформаційних технологій в економічних відносинах суб'єктів ринку, що потребує нових підходів до маркетингової діяльності підприємств. Інформаційні технології значною мірою впливають на функціонування кожної підсистеми маркетингу, створюючи нові можливості та загрози.…”
Section: Of Performance Indicators For Communication Activity Of Enteunclassified
“…У своїх працях дослідники [1] наголошують на значній ролі інформаційних технологій в економічних відносинах суб'єктів ринку, що потребує нових підходів до маркетингової діяльності підприємств. Інформаційні технології значною мірою впливають на функціонування кожної підсистеми маркетингу, створюючи нові можливості та загрози.…”
Section: Of Performance Indicators For Communication Activity Of Enteunclassified
“…The rise of online shopping is shaping ways in which business is conducted. Wang and Qu (2017) indicated that the rapid development of the Internet, mobile phones, tablet computers, and the electronic devices has changed the way people shop. Online shopping is increasingly becoming popular among buyers of almost all products, including fresh produce.…”
Section: Introductionmentioning
confidence: 99%
“…The online shopping is definitely having some adverse consequences for the offline market arrangements. It is also causing many physical stores to shut down (Wang & Qu, 2017). For example, Staples, JCPenney, and Sears stores have all decided to close some of their brick and mortar stores in many areas.…”
Section: Introductionmentioning
confidence: 99%
“…In their papers, researchers (Wang, M., & Qu, H. 2017) emphasize the significant role of information technology in economic relations of market players, which requires new approaches to marketing activities of enterprises. Information technology greatly affects the functioning of each subsystem of marketing, creating new opportunities and threats.…”
Section: Introductionmentioning
confidence: 99%